Відповідь:
1) f(2) = 2,5
f(-1) = -2
f(3) = [tex]3\frac{1}{3}[/tex]
f(а) = [tex]\frac{a^{2} + 1}{a}[/tex]
2) g(0) = -3
g(1) = -2
g(-2) = 1
g(b) = b² - 3
3) φ(0) = 1 або -1
φ(3) = 2 або -2
φ(-1) = 0
φ(m) = [tex]\sqrt{m + 1}[/tex]
Пояснення:
1) f(x) = x + 1/x у точках 2, -1, 3, а
Підставимо замість x значення даних точок:
f(2) = 2 + 1/2 = 2,5
f(-1) = -1 + 1/(-1) = -1 - 1 = -2
f(3) = 3 + 1/3 = [tex]3\frac{1}{3}[/tex]
f(а) = а + 1/а = [tex]\frac{a^{2} + 1}{a}[/tex]
2) g(x) = x² - 3 у точках 0, 1, -2, b
g(0) = 0² - 3 = 0 -3 = -3
g(1) = 1² - 3 = 1- 3 = -2
g(-2) = (-2)² - 3 = 4 - 3 = 1
3) φ(x) = [tex]\sqrt{x + 1}[/tex] у точках 0, 3, -1, m
φ(0) = [tex]\sqrt{0 + 1}[/tex] = √1 = 1 або -1
φ(3) = [tex]\sqrt{3 + 1}[/tex] = √4 = 2 або -2
φ(-1) = [tex]\sqrt{-1 + 1}[/tex] = √0 = 0
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь:
1) f(2) = 2,5
f(-1) = -2
f(3) = [tex]3\frac{1}{3}[/tex]
f(а) = [tex]\frac{a^{2} + 1}{a}[/tex]
2) g(0) = -3
g(1) = -2
g(-2) = 1
g(b) = b² - 3
3) φ(0) = 1 або -1
φ(3) = 2 або -2
φ(-1) = 0
φ(m) = [tex]\sqrt{m + 1}[/tex]
Пояснення:
1) f(x) = x + 1/x у точках 2, -1, 3, а
Підставимо замість x значення даних точок:
f(2) = 2 + 1/2 = 2,5
f(-1) = -1 + 1/(-1) = -1 - 1 = -2
f(3) = 3 + 1/3 = [tex]3\frac{1}{3}[/tex]
f(а) = а + 1/а = [tex]\frac{a^{2} + 1}{a}[/tex]
2) g(x) = x² - 3 у точках 0, 1, -2, b
Підставимо замість x значення даних точок:
g(0) = 0² - 3 = 0 -3 = -3
g(1) = 1² - 3 = 1- 3 = -2
g(-2) = (-2)² - 3 = 4 - 3 = 1
g(b) = b² - 3
3) φ(x) = [tex]\sqrt{x + 1}[/tex] у точках 0, 3, -1, m
Підставимо замість x значення даних точок:
φ(0) = [tex]\sqrt{0 + 1}[/tex] = √1 = 1 або -1
φ(3) = [tex]\sqrt{3 + 1}[/tex] = √4 = 2 або -2
φ(-1) = [tex]\sqrt{-1 + 1}[/tex] = √0 = 0
φ(m) = [tex]\sqrt{m + 1}[/tex]